Clinical Efficacy of Different Thoracoscopic Surgeries for Patients With Non-small Cell Lung Cancer - Wang, Tao; Liu, Xi; Chen, Lei; Liang, Tao; Ning, Xiaokuang (Frontiers in Surgery, 2022)
Background: The aim of this study was to analyze the clinical efficacy of different thoracoscopic procedures in patients with non-small cell lung cancer and their correlation with matrix metalloproteinase-7 mRNA (mmp-7 mRNA) and soluble major histocompatibility complex class I molecule A (sMICA), as well as their effect on T-cell subsets. Methods: A total of 100 patients with non-small cell lung cancer who received different thoracoscopic surgeries were divided into Control group (three-port thoracoscopic surgery) and study group (single-port thoracoscopic surgery). The two groups were evaluated to compare the perioperative indicators, mmp -7 mRNA, sMICA expression levels, T cell subsets, postoperative pain, complication rates, and prognostic outcomes at 1 year follow-up Results: The operation time, blood loss, drainage tube placement time, incision length, and hospital stay in the study group were less than those in the control group (P < 0.05); there was no significant difference in the number of lymph node dissections between the two groups (P > 0.05); After 3 days, the expression levels of MMPs-7 mRNA and sMICA in the study group were lower than those in the control group (P < 0.05); CD4 +, CD8 +, CD4 +/CD8 + in the study group were higher than those in the control group (P < 0.05). On 1d, 3d, and 5d, Fig. The visual analogue score (VAS) of the study group was lower than that of the control group (P < 0.05); there was no significant difference in the complication rate between the two follow-up groups (P > 0.05); all patients completed the follow-up. After 1 year of follow-up, there was no significant difference in the tumor-free survival rate and overall survival rate between the two groups (P > 0.05). Conclusion: Compared with three-port thoracoscopic surgery, single-port thoracoscopic surgery can improve perioperative expression, shorten hospital stay, reduce serum tumour micrometastasis levels, improve immune metastasis mechanisms and reduce pain, which is of great significance to patients with non-small cell lung cancer. It is an effective, convenient and safe surgical option that deserves wide clinical reference.